2021
DOI: 10.1002/gj.4150
|View full text |Cite
|
Sign up to set email alerts
|

Fluid inclusions, stable isotopes (H–O–S), and age constraints on the genesis of the Basitielieke polymetallic tungsten deposit in the Altay, Xinjiang, NW China

Abstract: The Chinese Altay in Northwest China and adjacent regions in the Russian and Mongolian Altay form a tungsten province within the Central Asian Orogenic Belt. Unlike the Russian and Mongolian Altay, almost no tungsten deposits in the Chinese Altay have been reported. The Basitielieke deposit located in the Altay orogenic belt in Xinjiang is a newly discovered polymetallic tungsten deposit hosted in the skarn in the exocontact zone of a granite pluton. Mineralization can be divided into the skarn period and supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…The granite porphyry samples were collected from the Keziergayin region in the Kelan Basin and intrude into the Kangbutiebao Formation. (Figure 2; Yang et al, 2017;Yang et al, 2019). The Kelan Basin lies in the Qiongkuer Domain (Figure 1B).…”
Section: Study Area Geology and Sample Collectionmentioning
confidence: 92%
“…The granite porphyry samples were collected from the Keziergayin region in the Kelan Basin and intrude into the Kangbutiebao Formation. (Figure 2; Yang et al, 2017;Yang et al, 2019). The Kelan Basin lies in the Qiongkuer Domain (Figure 1B).…”
Section: Study Area Geology and Sample Collectionmentioning
confidence: 92%
“…Wang et al (2012b) and Ding et al (2012) reported that Zaia and Xueru are small skarn Fe deposits that occur in the contact zone between the granodiorite (80 Ma) and the Lower Cretaceous Langshan limestone, but the amount of the resource remains unclear. Zhanting, Meihuashan, Congbari, Pianqu, Bangai, and Wuluqiong prospects were formed in Frontiers in Earth Science frontiersin.org the contact zone between the intermediate-felsic intrusive rocks (161-157 Ma) and carbonate rocks (Yang et al, 2018). Porphyritic intrusions are found in most of those skarn deposits and mostly are granodiorite, diorite, and monzonite (Figure 6).…”
Section: Skarn Copper and Iron Depositsmentioning
confidence: 99%